The DHA supplementation during pregnancy: benefits and risks - review - Dutkiewicz, Justyna; Mączyńska, Wiktoria; Wijata , Michał; Wijata , Anna Maria; Przybyłek-Stępień, Zuzanna Adriana; Bartosiński, Ryszard; Szustak, Jan; Kąpa, Maria; Szepietowski, Bartosz; Kaźmierczak, Jakub Marek; et al. (Journal of Education, Health and Sport, 2025)
Pregnancy is a special period in a woman’s life that requires special attention. For the proper development of the foetus and the maintenance of the mother’s health, a balanced diet and appropriate supplementation are extremely important. One of the key nutrients is docosahexaenoic acid (DHA), which belongs to the group of polyunsaturated omega-3 fatty acids. The present paper reviews the literature on the biological significance of DHA during pregnancy, as well as the sources of this nutrient and its requirement. The benefits of taking DHA are also presented. The potential risks and limitations of DHA supplementation are discussed, including the risks of contaminants present in fish products. International recommendations and future research directions are also presented, highlighting the need for further analysis of the impact of DHA on the long-term health of both mother and child. Objective: This thesis aims to review the scientific literature on the biological importance of DHA during pregnancy, the sources and need for this ingredient and the benefits of supplementation. The text will also address the potential risks and limitations of DHA intake, international recommendations, and future research directions in this field. Materials and methods: The review includes scientific papers and literature reviews published in the last 15 years 2010-2025, available in the PubMed and Google Scholar databases, which were identified using relevant keywords such as DHA supplementation and pregnancy. Polish and international recommendations were also included in the analysis. Conclusions: DHA supplementation during pregnancy is particularly important for the development of the fetal brain and vision, as well as for the prevention of pregnancy complications. However, there is a lack of precise data on optimal doses and desired DHA concentrations in the blood. Future studies should focus on these issues and the long-term effects of DHA supplementation.